Daily rhythms of TNFα expression and food intake regulate synchrony of Plasmodium stages with the host circadian cycle - Hirako, Isabella Cristina (Cell Host Microbe, 2018)
The Plasmodium cell cycle, wherein millions of parasites differentiate and proliferate, occurs in synchrony with the vertebrate host’s circadian cycle. The underlying mechanisms are unknown. Here we addressed this question in a mouse model of Plasmodium chabaudi infection. Inflammatory gene expression and carbohydrate metabolism are both enhanced in IFNγ-primed leukocytes and liver cells from P. chabaudi-infected mice. TNFα expression oscillates across the host circadian cycle, and increased TNFα correlates with hypoglycemia and a higher frequency of non-replicative ring forms of trophozoites. Conversly, parasites proliferate and acquire biomass during food intake by the host. Importantly, cyclic hypoglycemia is attenuated and synchronization of P. chabaudi stages is disrupted in IFNγ(−/−), TNF receptor(−/−) or diabetic mice. Hence, the daily rhythm of systemic TNFα production and host food intake set the pace for Plasmodium synchronization with host’s circadian cycle. This mechanism indicates that Plasmodium parasites take advantage of the host’s feeding habits.